Variants of Topology Editing Strategy in the Subsystem of Printed Circuit Boards Manufacturability Improvement - Panchak, R.; Kolesnyk, K.; Lobur, M. (ХНУРЭ, 2011)
This paper focuses on the variants of printed circuit boards topology editing strategies implemented in the subsystem of automatic printed circuit boards topology editing. Depending on the requirements for printed circuit board topology, a subsystem user can create variants of editing strategies in order to minimize the amount of the technologically justified places with a minimum clearance between the elements of the topology.
Keywords: printed circuit board manufacturability; printed circuit board topology